Bone Engineering Scaffolds With Exosomes: A Promising Strategy for Bone Defects Repair - Zhang, Mingming; Li, Yi; Feng, Taojin; Li, Ran; Wang, Zhongqi; Zhang, Licheng; Yin, Pengbin; Tang, Peifu (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of bone defects is still an intractable clinical problem, despite the fact that numerous treatments are available currently. In recent decades, bone engineering scaffolds have become a promising tool to fill in the defect sites and remedy the deficiency of bone grafts. The combination of bone engineering scaffolds with cell-based and cell-free therapy greatly promotes osteogenesis, angiogenesis and inflammation modulation, which are widely used in bone defects repair. As a key element of cell-free therapy, exosomes with nucleic acids, proteins, lipids and metabolites, overcome the deficiencies of cell-based therapy and promote the bone regeneration via the potential of osteogenesis, angiogenesis and inflammation modulation. Hence, this review aims at overviewing bone defect microenvironment and healing mechanism, summarizing current advances of bone engineering scaffolds and exosomes in bone defects as to probe for future applications.